2015
DOI: 10.1371/journal.pone.0138829
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Cord Clamping and Neonatal Outcomes in Very Preterm Infants

Abstract: BackgroundDelayed cord clamping (DCC, ≥30s) increases blood volume in newborns and is associated with fewer blood transfusions and short-term neonatal complications. The optimal timing of cord clamping for very preterm infants should maximize placental transfusion without interfering with stabilization and resuscitation.AimWe compared the effect of different durations of DCC, 30-45s vs. 60-75s, on delivery room (DR) and neonatal outcomes in preterm infants <32 weeks gestational age (GA).MethodsThis is a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 29 publications
2
34
0
Order By: Relevance
“…There is not a consensus on the optimal timing of delay, but one quality improvement study in very preterm infants found that increasing the duration from 30 to 45seconds to 60 to 75 seconds is associated with decreased hypothermia on admission, neonatal respiratory interventions, and red blood cell transfusions without increase in neonatal mortality and morbidities. 18 Our study was consistent with prior research indicating that cesarean delivery may be associated with decreased likelihood of receiving DCC. 19 A survey of practitioners in the United Kingdom found that the most commonly expressed concern detracting from DCC was maternal bleeding at cesarean section, especially with less experienced obstetricians.…”
Section: Discussionsupporting
confidence: 91%
“…There is not a consensus on the optimal timing of delay, but one quality improvement study in very preterm infants found that increasing the duration from 30 to 45seconds to 60 to 75 seconds is associated with decreased hypothermia on admission, neonatal respiratory interventions, and red blood cell transfusions without increase in neonatal mortality and morbidities. 18 Our study was consistent with prior research indicating that cesarean delivery may be associated with decreased likelihood of receiving DCC. 19 A survey of practitioners in the United Kingdom found that the most commonly expressed concern detracting from DCC was maternal bleeding at cesarean section, especially with less experienced obstetricians.…”
Section: Discussionsupporting
confidence: 91%
“…We also evaluated the impact of DCC on hypothermia. Its benefits have been shown by several randomized trials, and include increased placental transfusion, cardiovascular stability, cerebral oxygenation and lower risk for both severe intraventricular haemorrhage and late-onset sepsis [17]. The higher duration of DCC (60-75 s) has also been associated with a lower incidence of hypothermia at birth in preterm infants [17].…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that our findings could be owing to improved cardiovascular stability and reduced fluctuations in cerebral blood flow, a lower number of fluid boluses, increased superior vena cava blood flow, and stable blood pressure after DCC. 22 , 23 , 24 , 25 , 26 , 27 …”
Section: Discussionmentioning
confidence: 99%